Development of 485 MPa Class High Strength Low Alloy Steel for Power Plant Infrastructures - Baskoro, Agung; Riastuti, Rini (UI Scholars Hub, 2024)
Currently, Indonesia is progressing to build 35,000 MW of power plants, which will increase the demand for materials, especially steel. One of these power plants is fossil fuel-based, which generates not only electricity but also flue gas containing sulfur that may cause corrosion to power plant infrastructure such as chimney or boiler areas. In addition, apart from being resistant to corrosion in sulfuric and hydrochloric acid conditions, the steel used in power plant infrastructure must also have good strength, toughness, and weldability. Therefore, the present paper describes about steel development for power plant applications that has not only corrosion resistance in sulfuric and hydrochloric acid environments but also good mechanical properties through the addition of vanadium as micro alloy element combined with the implementation of a thermo-mechanical controlled process (TMCP) in hot rolling process. The results showed that chemical composition and mechanical properties of the product comply with the standards ASTM A588 Grade A for high strength low alloy steel with atmospheric corrosion resistance. The measured atmospheric corrosion index is 6.54. Thus, the mechanical properties of the steel produced are yield strength of 512-518 MPa, tensile strength of 662-664 MPa, and elongation of 40-42%. The microstructure of the product is ferrite and perlite, with an average grain size of ASTM No. 12.10 (5.2-5.5 µm) classified as very fine grain.